An empirical analysis of talent policy, executive incentive, and enterprise green technological innovation based on China’s A-share listed companies - Zhang, Yuan-Bo; Qu, Shi-You; Li, Hai-Bo; Li, Miao-Miao (Frontiers in Environmental Science, 2022)
This article investigates how talent policies affect corporate green technological innovation through executive incentive strategies based on signaling theory and principal-agent theory, by examining samples from 1,536 A-share listed companies between 2010 and 2020. The findings indicate that talent policy helps enterprises boost green technological innovation while accelerating it by improving executive compensation incentives. This effect path is more significant in high-tech enterprises and enterprises with weak solvency ratios. However, we find that the current talent policy has inhibited the green innovation of enterprises. The conclusions provide micro-evidence for the impact mechanism by which talent policy affects enterprise green technological innovation and offer scientifically based guidelines for optimizing talent policy to promote innovation-driven development strategy.